A SNARE geranylgeranyltransferase essential for the organization of the Golgi apparatus. (3rd March 2020) - Shirakawa, Ryutaro; Goto‐Ito, Sakurako; Goto, Kota; Wakayama, Shonosuke; Kubo, Haremaru; Sakata, Natsumi; Trinh, Duc Anh; Yamagata, Atsushi; Sato, Yusuke; Masumoto, Hiroshi; Cheng, Jinglei; Fujimoto, Toyoshi; et al.
Abstract: Protein prenylation is essential for many cellular processes including signal transduction, cytoskeletal reorganization, and membrane trafficking. Here, we identify a novel type of protein prenyltransferase, which we named geranylgeranyltransferase type‐III (GGTase‐III). GGTase‐III consists of prenyltransferase alpha subunit repeat containing 1 (PTAR1) and the β subunit of RabGGTase. Using a biotinylated geranylgeranyl analogue, we identified the Golgi SNARE protein Ykt6 as a substrate of GGTase‐III. GGTase‐III transfers a geranylgeranyl group to mono‐farnesylated Ykt6, generating doubly prenylated Ykt6. The crystal structure of GGTase‐III in complex with Ykt6 provides structural basis for Ykt6 double prenylation. In GGTase‐III‐deficient cells, Ykt6 remained in a singly prenylated form, and the Golgi SNARE complex assembly was severely impaired. Consequently, the Golgi apparatus was structurally disorganized, and intra‐Golgi protein trafficking was delayed. Our findings reveal a fourth type of protein prenyltransferase that generates geranylgeranyl‐farnesyl Ykt6. Double prenylation of Ykt6 is essential for the structural and functional organization of the Golgi apparatus. Synopsis: Three types of protein prenyltransferases are known to catalyse protein farnesylation and geranylgeranylation in eukaryotic cells. Here, a fourth class formed by PTAR1 heterodimerization with RabGGTβ is found to drive double prenylation of Golgi SNARE Ykt6, which is critical for Golgi complex maintenance and function in mammalian cells. Human PTAR1 and RabGGTβ form a fourth type of protein prenyltransferase, named GGTase‐III. GGTase‐III transfers a geranylgeranyl group to mono‐farnesylated Ykt6, generating doubly‐prenylated Ykt6. Structural analyses reveal the catalytic mechanism of Ykt6 double prenylation. Doubly‐prenylated Ykt6 is required for maintaining structure and function of the Golgi apparatus. Abstract : A new type of protein prenyltransferase formed by PTAR1 and RabGGTβ heterodimers drives double prenylation of Golgi SNARE Ykt6, which is critical for Golgi complex maintenance and function in mammalian cells.